Activated microglia in a rat stroke model express NG2 proteoglycan in peri‐infarct tissue through the involvement of TGF‐β1. Issue 2 (6th December 2013) - Sugimoto, Kana; Nishioka, Ryutaro; Ikeda, Airi; Mise, Ayano; Takahashi, Hisaaki; Yano, Hajime; Kumon, Yoshiaki; Ohnishi, Takanori; Tanaka, Junya
<x xml:space="preserve">Abstract</x> We investigated activated microglia in ischemic brain lesions from rats that had been subjected to transient middle cerebral artery occlusion. Activated microglia expressing NG2 chondroitin sulfate proteoglycan (NG2) were found only in the narrow zone (demarcation zone) that demarcated the peri‐infarct tissue and ischemic core. NG2− activated microglia were abundantly distributed in the peri‐infarct tissue outside the demarcation zone. NG2+ microglia but not NG2− microglia expressed both CD68 and a triggering receptor expressed on myeloid cells 2 (TREM‐2), suggesting that NG2+ microglia eliminated apoptotic neurons. In fact, NG2+ microglia often attached to degenerating neurons and sometimes internalized NeuN+ or neurofilament protein+ material. Kinetic studies using quantitative real‐time RT‐PCR revealed that expression of transforming growth factor‐β1 (TGF‐β1) was most evident in the ischemic core; with this marker produced mainly by macrophages located in this region. TGF‐β receptor mRNA expression peaked at 3 days post reperfusion (dpr) in the peri‐infarct tissue, including the demarcation zone. Primary cultured rat microglia also expressed the receptor mRNA. In response to TGF‐β1, primary microglia enhanced the expression of NG2 protein and TREM‐2 mRNA as well as migratory activity. A TGF‐β1 inhibitor, SB525334, abolished these effects. The present results suggest that TGF‐β1 produced in the ischemic core diffused toward the peri‐infarct tissue, driving activated microglial cells to eliminate degenerating neurons. Appropriate control of NG2+ microglia in the demarcation zone might be a novel target for the suppression of secondary neurodegeneration in the peri‐infarct tissue. GLIA 2014;62:185–198